ANALISIS LAPORAN REALISASI ANGGARAN KHUSUS KELURAHAN (AKK) 2016-2017 STUDI KASUS (KELURAHAN ADIARSA BARAT KABUPATEN KARAWANG) - Sri Suartini (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
APBD is a plan for the implementation of all Regional Revenues and all Regional Expenditures in the framework of the implementation of Decentralization within a given fiscal year. Collection of all Regional revenues aims to meet the targets set in the APBD. Likewise, all regional expenditures and bonds that burden the regions in the context of the implementation of decentralization are carried out in accordance with the amounts and targets set in the APBD. Because the APBD is the basis for regional financial management, the APBD also forms the basis for regional financial control, inspection and supervision activities Basically, the performance budget is a system for preparing and managing regional budgets which are oriented towards achieving results or performance. The performance must reflect the efficiency and effectiveness of public services, which means it must be oriented to the public interest. This has become the need of regional communities to carry out broad, real and responsible autonomy and regional autonomy must be understood as the right or authority of local communities to manage and manage their own affairs. The aspect or role of the regional government is no longer a mere tool of the interests of the central government but rather a tool to fight for regional aspirations and interests. The method used, the process of collecting data moves from the empirical field in an effort to build theory from the data, the purpose of this study is to find out, understand and analyze how the Reporting and Presentation of 2016-2017 Urban Budget Special Realization (AKK) in Adiarsa Barat District, Karawang Barat District Karawang and analyze how the financial analysis of 2016-2017 Urban Budget Special Realization (AKK) in Adiarsa Barat Village Karawang Barat District Karawang District. By paying attention to these objectives, the research method used is a Quantitative Description Adiarsa Barat Kelurahan shopping performance from T 2016 to T.A 2017 showed good performance. Based on the analysis of the results of the 2016/2017 T.A shopping growth shows there is a growth in spending. Expenditures which most affected the increase in growth in total expenditure were capital and operational expenditure